Expanding Phenotype of Schimke Immuno-Osseous Dysplasia: Congenital Anomalies of the Kidneys and of the Urinary Tract and Alteration of NK Cells - Cristina Bertulli (International Journal of Molecular Sciences, 2020)
Schimke immuno-osseous dysplasia (SIOD) is a rare multisystemic disorder with a variable clinical expressivity caused by biallelic variants in SMARCAL1. A phenotype–genotype correlation has been attempted and variable expressivity of biallelic SMARCAL1 variants may be associated with environmental and genetic disturbances of gene expression. We describe two siblings born from consanguineous parents with a diagnosis of SIOD revealed by whole exome sequencing (WES). Results: A homozygous missense variant in the SMARCAL1 gene (c.1682G>A; p.Arg561His) was identified in both patients. Despite carrying the same variant, the two patients showed substantial renal and immunological phenotypic differences. We describe features not previously associated with SIOD—both patients had congenital anomalies of the kidneys and of the urinary tract and one of them succumbed to a classical type congenital mesoblastic nephroma. We performed an extensive characterization of the immunophenotype showing combined immunodeficiency characterized by a profound lymphopenia, lack of thymic output, defective IL-7Rα expression, and disturbed B plasma cells differentiation and immunoglobulin production in addition to an altered NK-cell phenotype and function. Conclusions: Overall, our results contribute to extending the phenotypic spectrum of features associated with SMARCAL1 mutations and to better characterizing the underlying immunologic disorder with critical implications for therapeutic and management strategies.